Construction and Validation of the Legitimizing Income Inequality Scale. (January 2022) - Coleman, Jeremy J.; Garriott, Patton O.; Kosmicki, Mia T.
Although income inequality has become a focus of political and social discourse, counseling psychology research examining correlates and consequences of legitimizing income inequality remains sparse. A significant barrier to the study of income inequality is the lack of available measures to assess attitudes toward socioeconomic inequality. The purpose of this study was to develop and provide initial validity evidence for the Legitimizing Income Inequality Scale (LIIS). Results supported a bifactor structure for the LIIS with a general factor (ω = .95) and subfactors measuring Social Welfare Beliefs (ω = .92), Economic Fatalism (ω = .87), and Economic Meritocracy Beliefs (ω = .90). The LIIS significantly correlated in theoretically consistent directions with scores on measures of classist attitudes, socioeconomic conservatism, impression management, and colorblind racial attitudes. Implications for future research and training using the LIIS are provided.